Demonstration of a high average power tabletop soft x-ray laser - Benware, B. R., author; Moreno, C. H., author; Macchietto, C. D., author; Rocca, Jorge J., author; American Physical Society, publisher (Colorado State University. Libraries, 1998)
We report the first demonstration of a high average power tabletop soft x-ray laser. An average laser output power of ≈1 mW (>2 × 1014 photons/s) was generated at 46.9 nm in Ne-like Ar using a very compact tabletop discharge. The spatially coherent average power emitted by this 26.5 eV laser is comparable to that generated at this photon energy in a similar bandwidth (Δλ/λ = 10-4) by a third generation synchrotron beam line. Lasing was obtained at a repetition rate of 7 Hz with an average output energy of 135 μJ/pulse by exciting a plasma column in a ceramic capillary with a fast current pulse. This very compact high-repetition-rate laser source makes intense short-wavelength coherent radiation accessible to a wide variety of new applications.